New electronic habit reminder for the management of thumb-sucking habit - Srinath Krishnappa; M S Rani; Sandeep Aariz (Wolters Kluwer Medknow Publications, 2016)
Methods for intervention of nonnutritive sucking habits include counseling, positive reinforcement, calendar with rewards, adhesive bandage, bitter nail polish, long sleeves, and appliance therapy. All these methods have been reported in the literature with variable success rates. We present a case of an 8-year-old child with thumb-sucking habit successfully managed in a short period of 5 months by a new electronic habit reminder, an extraoral appliance which was designed to overcome the disadvantages associated with intraoral appliances.